Health state utilities associated with attributes of weekly injection devices for treatment of type 2 diabetes - Matza, Louis S. (BMC Health Serv Res, 2017)
BACKGROUND: Glucagon-like peptide-1 (GLP-1) receptor agonists are often recommended as part of combination therapy for type 2 diabetes when oral medication does not result in sufficient glycemic control. Several GLP-1 receptor agonists are available as weekly injections. These medications vary in their injection delivery systems, and these differences could impact quality of life and treatment preference. The purpose of this study was to estimate utilities associated with attributes of injection delivery systems for weekly GLP-1 therapies. METHODS: Participants with type 2 diabetes in the UK valued health states in time trade-off interviews. The health states (drafted based on literature, device instructions for use, and clinician interviews) had identical descriptions of type 2 diabetes, but differed in description of the treatment process. One health state described oral treatment, while six others described oral treatment plus a weekly injection. The injection health states varied in three aspects of the treatment administration process: requirements for reconstituting the medication (i.e., mixing the medication prior to the injection), waiting during medication preparation, and needle handling. Every participant valued all seven health states. RESULTS: A total of 209 participants completed interviews (57.4% male; mean age = 60.4y). The mean utility of the oral treatment health state was 0.89. All injection health states had significantly (p < 0.01) lower utilities ranging from 0.86 to 0.88. Differences among health state utilities suggest that each administration requirement had a small but measureable disutility: -0.004 (reconstitution), -0.004 (needle handling), -0.010 (reconstitution, needle handling), and -0.020 (reconstitution, waiting, needle handling). CONCLUSIONS: Findings suggest it is feasible to use the TTO method to quantify preferences among injection treatment processes. It may be useful to incorporate these utility differences into cost-utility models comparing weekly injectable treatments for patients with type 2 diabetes.